2021
DOI: 10.1101/2021.07.02.450777
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neutrophil and natural killer cell imbalances prevent muscle stem cell mediated regeneration following murine volumetric muscle loss

Abstract: Volumetric muscle loss (VML) overwhelms the innate regenerative capacity of mammalian skeletal muscle (SkM), leading to numerous disabilities and reduced quality of life. Immune cells are critical responders to muscle injury and guide tissue resident stem cell and progenitor mediated myogenic repair. However, how immune cell infiltration and inter-cellular communication networks with muscle stem cells are altered following VML and drive pathological outcomes remains underexplored. Herein, we contrast the cellu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(31 citation statements)
references
References 85 publications
9
22
0
Order By: Relevance
“…To understand the fibrotic response that develops after VML, we administered 2mm full-thickness punch biopsies to the tibialis anterior (TA) muscles of young adult mice. Consistent with previous results 9 , we observed increased fibrosis by staining with picrosirius red at 7- and 28-days post injury (dpi) (Supp. Figure 1A).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…To understand the fibrotic response that develops after VML, we administered 2mm full-thickness punch biopsies to the tibialis anterior (TA) muscles of young adult mice. Consistent with previous results 9 , we observed increased fibrosis by staining with picrosirius red at 7- and 28-days post injury (dpi) (Supp. Figure 1A).…”
Section: Resultssupporting
confidence: 92%
“…In line with these observations, we observed increases in expression of NK cell-related transcripts with ITD1 treatment. Prior work from our group has shown that NK cell infiltration into VML injuries reduces neutrophil abundance, and that the neutrophil secretome impairs myogenesis in vitro 9 . Thus, enhanced NK cell activity and restrained inflammation from neutrophils as a result of TGFBR2 inhibition could be one mechanism through which this intervention contributes to a more favorable biochemical environment for muscle regeneration.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations